Fungal Associates of Soft Scale Insects (Coccomorpha: Coccidae) - Teresa Szklarzewicz; Katarzyna Michalik; Beata Grzywacz; Małgorzata Kalandyk-Kołodziejczyk; Anna Michalik (Cells, 2021)
Ophiocordyceps fungi are commonly known as virulent, specialized entomopathogens; however, recent studies indicate that fungi belonging to the Ophiocordycypitaceae family may also reside in symbiotic interaction with their host insect. In this paper, we demonstrate that Ophiocordyceps fungi may be obligatory symbionts of sap-sucking hemipterans. We investigated the symbiotic systems of eight Polish species of scale insects of Coccidae family: Parthenolecanium corni, Parthenolecanium fletcheri, Parthenolecanium pomeranicum, Psilococcus ruber, Sphaerolecanium prunasti, Eriopeltis festucae, Lecanopsis formicarum and Eulecanium tiliae. Our histological, ultrastructural and molecular analyses showed that all these species host fungal symbionts in the fat body cells. Analyses of ITS2 and Beta-tubulin gene sequences, as well as fluorescence in situ hybridization, confirmed that they should all be classified to the genus Ophiocordyceps. The essential role of the fungal symbionts observed in the biology of the soft scale insects examined was confirmed by their transovarial transmission between generations. In this paper, the consecutive stages of fungal symbiont transmission were analyzed under TEM for the first time.